ENEAGRAM SEBAGAI PETA GAMBARAN DIRI - John Tondowidjojo (Bahasa Indonesia, 2018)
The Enneagram is a personality type system of nine interconnected personality archetypes. These nine types are connected to the other four composed around the symbolic diagram. The Enneagram symbol has an ancient and mysterious origin. This symbol is an elegant model of some basic laws of the universe expressed in mathematical terms that reflect patterns seen in nature, including in the human ego or personality. Archetypes are models or prototypes that help us distinguish and understand the universal pattern. According to Carl Jung, the archetype is a "distinctive mode of understanding" (the pattern of psychic perception and common understanding for all humans), Jung takes the archetypal concept of ancient Greece, which sees the world in terms of archetypal principles, reflecting the cosmic vision as an expression ruled by A particular primordial essence or a transcendent first principle. Carolyn Myss defines archetypes as "the psychic lens through which we see ourselves and the world around us."Enneagram is able to target and handle the most important inner conflicts in human beings. Using the Enneagram map, human beings are able to define and understand key issues and thereafter provide a way to work.